Quantitation of human cellular retinoic acid-binding protein II (CRABP-II) RNA from cultured human skin fibroblast cells and human skin biopsies treated with retinoic acid. - Zhou, L (1992)
A polymerase chain reaction (PCR) method has been validated for the quantitation of retinoic acid (RA) induction of cellular retinoic acid-binding protein II (CRABP-II) RNA from cultured human skin fibroblasts and human skin biopsies. The method utilizes reverse transcription and PCR (RT-PCR) to compare cellular CRABP-II RNA with a known amount of added internal standard RNA generated from a modified CRABP-II cDNA containing a 42 bp deletion. Thus, after RT-PCR of cellular and standard CRABP-II RNA in the same tube, the resulting DNA bands could be distinguished by size on ethidium bromide-stained, nondenaturing polyacrylamide gel. Serial dilutions of cellular RNA were co-amplified with a fixed amount of internal standard CRABP-II RNA, and the ratio of intensities of the two DNA bands was determined by computerized image analysis of the gel photograph. A linear relationship was found between the logs of this ratio and the input RNA. Absolute quantitation of cellular CRABP-II RNA was determined from the 'equivalence point', the dilution at which band intensities from cellular and standard RNAs were identical. Using this quantitative assay, the amount of CRABP-II RNA in cultured fibroblasts was 24 attomoles per microgram total RNA. A 4.2-fold increase in CRABP-II RNA was seen following 24 hours treatment with 10(-6) M RA. CRABP-II RNA content in skin biopsies taken from 3 human subjects ranged from 16 to 25 attomole/micrograms RNA. Topical treatment with 0.1% RA cream resulted in induction ranging from 3.9- to 12-fold over vehicle treatment. The method described here offers a rapid, sensitive and quantitative assay of specific RNAs, and should be especially useful for the measurement of RNA levels from small solid-tissue biopsies.